Role of Neo-Sinus on Thrombogenicity of Aortic Valve Prostheses: Experimental Proof-of-Concept Study - Saskia Thoenissen; Ilona Mager; Claudio A. Luisi; Markus Mous; Thomas Schmitz-Rode; Ulrich Steinseifer; Johanna C. Clauser (Cardiovascular Engineering and Technology, 2025)
Purpose Transcatheter aortic valve replacement (TAVR) is the standard treatment for patients with aortic diseases at high surgical risk. Transcatheter heart valve prostheses (THV) are inserted into the aortic valve, creating a new area between the native and artificial leaflets. This area, known as neo-sinus, increases the thrombogenicity of THVs. But there is a lack of testing methods that evaluate thrombogenicity in vitro. Methods To analyze the flow field within the native sinus and the neo-sinus, Particle Image Velocimetry (PIV) was performed with a thrombosis tester. Additionally, a comparative study was conducted with porcine blood on two polycarbonate urethane valves, with and without neo-sinus, respectively. Blood samples collected every hour were analyzed for platelet count, coagulation via ROTEM parameters, and plasma-free hemoglobin. Thrombus formation was detected optically. Results The PIV measurements yield a physiological flow field in the aortic root that were consistent with those reported in literature. The analyzed blood parameters reveal no obvious difference between the valve with neo-sinus and the valve without. A higher amount of thrombus material for the valve with neo-sinus was found. Conclusion The visualized flow field shows low velocities and stagnation zones due to the presence of native leaflets. Clot formation at the heart valve prostheses are in accordance with in-vivo findings. The benchmark of the two valves indicates an increased thrombogenic potential due to the neo-sinus. The thrombosis tester simulates the natural environment after TAVR. Thereby, newly developed THVs can be evaluated in vitro and consequently optimized regarding their thrombogenicity.

In-Vitro Visualization of Thrombus Growth in Artificial Lungs Using Real-Time X-Ray Imaging: A Feasibility Study - Andreas Kaesler; Freya Lilli Rudawski; Mark Oliver Zander; Felix Hesselmann; Isaac Pinar; Thomas Schmitz-Rode; Jutta Arens; Ulrich Steinseifer; Johanna Charlotte Clauser (Cardiovascular Engineering and Technology, 2022)
Purpose Extracorporeal membrane oxygenation has gained increasing attention in the treatment of patients with acute and chronic cardiopulmonary and respiratory failure. However, clotting within the oxygenators or other components of the extracorporeal circuit remains a major complication that necessitates at least a device exchange and bears risks of adverse events for the patients. In order to better predict thrombus growth within oxygenators, we present an approach for in-vitro visualization of thrombus growth using real-time X-ray imaging. Methods An in-vitro test setup was developed using low-dose anticoagulated ovine blood and allowing for thrombus growth within 4 h. The setup was installed in a custom-made X-ray setup that uses phase-contrast for imaging, thus providing enhanced soft-tissue contrast, which improves the differentiation between blood and potential thrombus growth. During experimentation, blood samples were drawn for the analysis of blood count, activated partial thromboplastin time and activated clotting time. Additionally, pressure and flow data was monitored and a full 360° X-ray scan was performed every 15 min. Results Thrombus formation indicated by a pressure drop and changing blood parameters was monitored in all three test devices. Red and white thrombi (higher/lower attenuation, respectively) were successfully segmented in one set of X-ray images. Conclusion We showed the feasibility of a new in-vitro method for real-time thrombus growth visualization by means of phase contrast X-ray imaging. In addition, with more blood parameters that are clinically relevant, this approach might contribute to improved oxygenator exchange protocols in the clinical routine.

Validation of a Miniaturized Test Loop for the Assessment of Human Blood Damage by Continuous-Flow Left-Ventricular Assist Devices - Eva Woelke; Ilona Mager; Thomas Schmitz-Rode; Ulrich Steinseifer; Johanna C. Clauser (Annals of Biomedical Engineering, 2021)
Despite improved hemocompatibility of left-ventricular assist devices (LVADs), assessment of blood damage remains mandatory in preclinical testing as standardized by ASTM-F1841. The most relevant test fluid is fresh, non-pooled human blood, but the limited volume of a standard donation requires significantly smaller loops than those commonly used with animal blood. In a recent study with porcine blood, we verified a miniaturized test loop with only 160 mL for the ASTM-conform paired testing of at least two LVADs and a static reference. Here, we validated this mini test loop for standardized assessment of blood damage with one 450-mL single donation of fresh human blood. Blood damage was assessed for HeartMate 3 and BPX-80 in 9 experiments with heparinized human blood for 6 hours. We analyzed plasma free hemoglobin, von Willebrand factor (vWF) concentration and collagen-binding functionality and calculated indices of hemolysis and vWF-ratios. Overall, we observed less blood damage compared to our previous study; however, the differences in mean indices of hemolysis and in mean normalized vWF-ratio between BPX-80 and HeartMate 3 were consistent for human blood. Thus, our mini test loop proved to be valid for preclinical standardized assessment of blood damage with only 450 mL of fresh human blood.

EndOxy: Dynamic Long-Term Evaluation of Endothelialized Gas Exchange Membranes for a Biohybrid Lung - Sarah Klein; Felix Hesselmann; Suzana Djeljadini; Tanja Berger; Anja Lena Thiebes; Thomas Schmitz-Rode; Stefan Jockenhoevel; Christian G Cornelissen (Annals of Biomedical Engineering, 2020)
In the concept of a biohybrid lung, endothelial cells seeded on gas exchange membranes form a non-thrombogenic an anti-inflammatory surface to overcome the lacking hemocompatibility of today’s oxygenators during extracorporeal membrane oxygenation. To evaluate this concept, the long-term stability and gas exchange performance of endothelialized RGD-conjugated polydimethylsiloxane (RGD-PDMS) membranes was evaluated. Human umbilical vein endothelial cells (ECs) were cultured on RGD-PDMS in a model system under physiological wall shear stress (WSS) of 0.5 Pa for up to 33 days. Gas exchange performance was tested with three biological replicates under elevated WSS of 2.5 Pa using porcine blood adjusted to venous values following ISO 7199 and blood gas analysis. EC morphology was assessed by immunocytochemistry ( n = 3). RGD-PDMS promoted endothelialization and stability of endothelialized membranes was shown for at least 33 days and for a maximal WSS of 2.5 Pa. Short-term exposure to porcine blood did not affect EC integrity. The gas transfer tests provided evidence for the oxygenation and decarboxylation of the blood across endothelialized membranes with a decrease of transfer rates over time that needs to be addressed in further studies with larger sample sizes. Our results demonstrate the general suitability of RGD-PDMS for biohybrid lung applications, which might enable long-term support of patients with chronic lung failure in the future.

Miniaturized Test Loop for the Assessment of Blood Damage by Continuous-Flow Left-Ventricular Assist Devices - Eva Woelke; Mario Klein; Ilona Mager; Thomas Schmitz-Rode; Ulrich Steinseifer; Jutta Arens; Johanna C. Clauser (Annals of Biomedical Engineering, 2020)

Mechanical Performance of Two Left Atrial Appendage Occlusion Systems: In Vitro Comparison of Tug Force, Radial Force, Sealing and Deformation - Matthias F. Menne; Jan W. Schrickel; Georg Nickenig; Baravan Al-Kassou; Dominik Nelles; Thomas Schmitz-Rode; Ulrich Steinseifer; Alexander Sedaghat (Annals of Biomedical Engineering, 2018)

A Novel Plasma-Based Fluid for Particle Image Velocimetry (PIV): In-Vitro Feasibility Study of Flow Diverter Effects in Aneurysm Model - Johanna Clauser; Marius S. Knieps; Martin Büsen; Andreas Ding; Thomas Schmitz-Rode; Ulrich Steinseifer; Jutta Arens; Giorgio Cattaneo (Annals of Biomedical Engineering, 2018)

VascuTrainer: A Mobile and Disposable Bioreactor System for the Conditioning of Tissue-Engineered Vascular Grafts - Frederic Wolf; Diana M. Rojas González; Ulrich Steinseifer; Markus Obdenbusch; Werner Herfs; Christian Brecher; Stefan Jockenhoevel; Petra Mela; Thomas Schmitz-Rode (Annals of Biomedical Engineering, 2018)

Development of an In Vitro PIV Setup for Preliminary Investigation of the Effects of Aortic Compliance on Flow Patterns and Hemodynamics - Martin Büsen; Christian Arenz; Michael Neidlin; Sam Liao; Thomas Schmitz-Rode; Ulrich Steinseifer; Simon J. Sonntag (Cardiovascular Engineering and Technology, 2017)

Fluid Dynamics in Rotary Piston Blood Pumps - Johannes Wappenschmidt; Simon J. Sonntag; Martin Buesen; Sascha Gross-Hardt; Tim Kaufmann; Thomas Schmitz-Rode; Ruediger Autschbach; Andreas Goetzenich (Annals of Biomedical Engineering, 2017)

Towards a Novel Spatially-Resolved Hemolysis Detection Method Using a Fluorescent Indicator and Loaded Ghost Cells: Proof-of-Principle - Sebastian V. Jansen; Indra Müller; Nicole Kiesendahl; Thomas Schmitz-Rode; Ulrich Steinseifer (Cardiovascular Engineering and Technology, 2015)

Particle Image Velocimetry Used to Qualitatively Validate Computational Fluid Dynamic Simulations in an Oxygenator: A Proof of Concept - Peter C. Schlanstein; Felix Hesselmann; Sebastian V. Jansen; Jeannine Gemsa; Tim A. Kaufmann; Michael Klaas; Dorothee Roggenkamp; Wolfgang Schröder; Thomas Schmitz-Rode; Ulrich Steinseifer; Jutta Arens (Cardiovascular Engineering and Technology, 2015)

Erratum to: Pulsatile Perfusion Bioreactor System for Durability Testing and Compliance Estimation of Tissue Engineered Vascular Grafts - Stefanos E. Diamantouros; Luis G. Hurtado-Aguilar; Thomas Schmitz-Rode; Petra Mela; Stefan Jockenhoevel (Annals of Biomedical Engineering, 2015)

Influence of the Measurement Plane on Aortic Annulus Indices: Structural and Clinical Implications - Maximilian Kütting; Alexander Sedaghat; Araceli White Tapia; Jan Roggenkamp; Nikos Werner; Thomas Schmitz-Rode; Ulrich Steinseifer (Cardiovascular Engineering and Technology, 2013)

Pulsatile Perfusion Bioreactor System for Durability Testing and Compliance Estimation of Tissue Engineered Vascular Grafts - Stefanos E. Diamantouros; Luis G. Hurtado-Aguilar; Thomas Schmitz-Rode; Petra Mela; Stefan Jockenhoevel (Annals of Biomedical Engineering, 2013)

Introduction of a method for quantitative evaluation of spontaneous motor activity development with age in infants - Catherine Disselhorst-Klug; Franziska Heinze; Nico Breitbach-Faller; Thomas Schmitz-Rode; Günter Rau (Experimental Brain Research, 2012)

Fibrin Gel as Alternative Scaffold for Respiratory Tissue Engineering - Christian G. Cornelissen; Maren Dietrich; Stefan Krüger; Jan Spillner; Thomas Schmitz-Rode; Stefan Jockenhoevel (Annals of Biomedical Engineering, 2012)

Integrated Home Monitoring and Compliance Optimization for Patients with Mechanical Circulatory Support Devices - Lars Klack; Thomas Schmitz-Rode; Wiktoria Wilkowska; Kai Kasugai; Felix Heidrich; Martina Ziefle (Annals of Biomedical Engineering, 2011)

Movement analysis by accelerometry of newborns and infants for the early detection of movement disorders due to infantile cerebral palsy - Franziska Heinze; Katharina Hesels; Nico Breitbach-Faller; Thomas Schmitz-Rode; Catherine Disselhorst-Klug (Medical & Biological Engineering & Computing, 2010)